2015
DOI: 10.1186/s12890-015-0063-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obstructive sleep apnea on lung volumes and mechanical properties of the respiratory system in overweight and obese individuals

Abstract: BackgroundEven through narrowing of the upper-airway plays an important role in the generation of obstructive sleep apnea (OSA), the peripheral airways is implicated in pre-obese and obese OSA patients, as a result of decreased lung volume and increased lung elastic recoil pressure, which, in turn, may aggravate upper-airway collapsibility.MethodsA total of 263 male (n = 193) and female (n = 70) subjects who were obese to various degrees without a history of lung diseases and an expiratory flow limitation, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…A possible conclusion could be that obesity within itself is a strong enough reducer of the ratio, regardless of the existence of OSA. 111,123 Based on this discovery alone and the fact that the OSA subjects of this study were obese, one could anticipate a reduced ratio, actually seen. 111,123…”
Section: Fev1/fvc Ratiomentioning
confidence: 79%
See 1 more Smart Citation
“…A possible conclusion could be that obesity within itself is a strong enough reducer of the ratio, regardless of the existence of OSA. 111,123 Based on this discovery alone and the fact that the OSA subjects of this study were obese, one could anticipate a reduced ratio, actually seen. 111,123…”
Section: Fev1/fvc Ratiomentioning
confidence: 79%
“…The fact that FVC predicted (%) was higher in the control group at rest compared to that of the experimental group for all sessions is well in accordance with the literature. 110,111 This variable has also been associated with the distance achieved during the 6MWT whereas shorter distances achieved were highly correlated with lower FVC predicted (%). 88 The same dynamic was observed in the current study.…”
Section: Fvc Predicted (%)mentioning
confidence: 99%
“…There was a tendency for a direct relationship between respiratory disturbance index (RDI) and overnight changes in forced expiratory volume in 1 s in OSA (p = 0.05, r = 0.30) Lung A reduction in end-tidal lung volumes may lead to a heightened potential for collapse of the upper airways [5]. Indeed, the relationship between reduced lung volume, increased respiratory resistance and increased severity of OSA is already described [2][3][4]. In keeping with these studies, we also found a significant, albeit weak association between spirometric indices and OSA severity.…”
Section: Discussionmentioning
confidence: 96%
“…OSA is a disorder which not only affects the upper airways but can also impact on the intra-thoracic airways. Indeed, reduced lung volumes, decreased elasticity and increased resistance of the lower airways are associated with more severe disease [2][3][4][5]. In addition, chronic airway diseases, including asthma and chronic obstructive pulmonary disease (COPD), influence the course of OSA [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…BMI showed a strong, independent and positive relation with asthma possibly because of the impact of adipose tissue on the chest wall causing a restrictive lung disease, but also as obesity is associated with a chronic inflammatory state (43,44). The pulmonary function tests (PFTs) of obese patients often show impaired expiratory reserve volume (ERV), functional residual capacity (FRC) and total lung capacity (TLC), secondary to increased abdominal load and disturbed chest wall mechanics (45,46).…”
Section: Airwaymentioning
confidence: 99%